Turning waste into value: Extraction and effective valorization strategies of seafood by-products - Felicia Ling Wen Xia; Sarifah Supri; Heder Djamaludin; Rahmi Nurdiani; Lim Leong Seng; Koh Wee Yin; Kobun Rovina (Elsevier, 2024)
Seafood by-products from various organisms like fish, shellfish, squids, and bivalves are often thrown away as waste, even though they could be utilized in creating new types of valuable foods. Up to 75% of the entire organism consists of industrial processing wastes, which can lead to a loss of profit and ecological sustainability if natural resources are not recycled efficiently. Various types of fish parts and byproducts, such as heads, viscera, skin, bones, scales, exoskeletons, pens, ink, and clam shells, can be categorized as valuable waste based on their weight percentages, which vary depending on the species and taxonomy. This review paper delves into the extraction and valorization strategies of seafood by-products, with a focus on transforming waste into valuable resources. Marine by-products can provide bioactive substances such as collagen, peptides, polyunsaturated fatty acids, antioxidants, chitin, and catalysts for biodiesel production. This review highlights the utilization of innovative techniques like microwave- and ultrasound-assisted extraction as well as supercritical fluid extraction and subcritical water extraction to extract bioactive compounds from seafood waste efficiently. This section also discusses the optimization of extraction processes to enhance efficiency and yield. Furthermore, the paper explores the potential applications of seafood by-products across various industries, emphasizing sustainable resource utilization and the creation of high-value products to be applied in our current circular economy.